The anti-inflammatory activity of GABA-enriched Moringa oleifera leaves produced by fermentation with Lactobacillus plantarum LK-1 - Zheng, Long; Lu, Xuli; Yang, Shengtao; Zou, Ying; Zeng, Fanke; Xiong, Shaohao; Cao, Yupo; Zhou, Wei (Frontiers in Nutrition, 2023)
Gamma-aminobutyric acid (GABA), one of the main active components in Moringa oleifera leaves, can be widely used to treat multiple diseases including inflammation. In this study, the anti-inflammatory activity and the underlying anti-inflammatory mechanism of the GABA-enriched Moringa oleifera leaves fermentation broth (MLFB) were investigated on lipopolysaccharide (LPS)-induced RAW 264.7 cells model. ELISA, RT-qPCR and Western blot results indicated that MLFB could dose-dependently inhibit the secretions and intracellular expression levels of pro-inflammatory cytokines like interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor-α (TNF-α). Furthermore, MLFB also suppressed the expressions of prostaglandin E2 (PGE2) and inducible nitric oxide synthase (iNOS). Moreover, the mRNA expressions of the key molecules like Toll-like receptor 4 (TLR-4) and nuclear factor (NF)-κB in the NF-κB signaling pathway were also restrained by MLFB in a dose-dependent manner. Our results indicated that the MLFB could effectively alleviate LPS-induced inflammatory response by inhibiting the secretions of pro-inflammatory cytokines and its underlying mechanism might be associated with the inhibition of TLR-4/NF-κB inflammatory signaling pathway activation. Besides, the key active components analysis result showed that the GABA, total polyphenols, and most organic acids like pyruvic acid, lactic acid as well as acetic acid were increased obviously after fermentation. The total flavonoids content in MLFB was still remained to be 32 mg/L though a downtrend was presented after fermentation. Therefore, the anti-inflammatory activity of MLFB might related to the relative high contents of GABA as well as other active constituents such as flavonoids, phenolics and organic acids in MLFB. Our study provides the theoretical basis for applying GABA-enriched Moringa oleifera leaves as a functional food ingredient in the precaution and treatment of chronic inflammatory diseases.